2005
DOI: 10.1002/gps.1275
|View full text |Cite
|
Sign up to set email alerts
|

Beyond the global score of the Zarit Burden Interview: useful dimensions for clinicians

Abstract: Three dimensions of burden were found: effect on the social and personal life of caregivers, psychological burden and feelings of guilt. Some health variables were linked to these dimensions. Spouses and children perceived burden differently. Spouse caregivers emphasized the deterioration of their personal and social life. Children, less involved in daily care, were more prone to feel guilt that they were not doing enough for their parent.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

18
182
3
14

Year Published

2005
2005
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 173 publications
(217 citation statements)
references
References 25 publications
18
182
3
14
Order By: Relevance
“…12 In contrast, a study of 152 primary caregivers of communitydwelling older adults with dementia in France yielded a mean (SD) ZBI score of 32.9 (17.9). 13 For the purpose of sample size calculation, we assumed the more conservative estimate (SD = 17.9). A sample size of 50 patients would yield a satisfactory precision (margin of error) of ± five points for a two-sided 95% confidence interval estimate around the mean change.…”
Section: Methodsmentioning
confidence: 99%
“…12 In contrast, a study of 152 primary caregivers of communitydwelling older adults with dementia in France yielded a mean (SD) ZBI score of 32.9 (17.9). 13 For the purpose of sample size calculation, we assumed the more conservative estimate (SD = 17.9). A sample size of 50 patients would yield a satisfactory precision (margin of error) of ± five points for a two-sided 95% confidence interval estimate around the mean change.…”
Section: Methodsmentioning
confidence: 99%
“…Some studies report that adult children show the highest levels of burden (Coen et al, 2002;Andrén and Elmståhl, 2007;Molyneux et al, 2008), whereas other state that the greatest burden is that experienced by spouse caregivers (Montgomery and Kosloski, 1994;Rinaldi et al, 2005;Serrano-Aguilar et al, 2006). Conversely, some authors have found no significant differences overall (Ferrario et al, 2003;Ankri et al, 2005;Turró-Garriga et al, 2008).…”
Section: Empirical Researchmentioning
confidence: 99%
“…Regarding specific features of the burden experienced by spouse and adult-child caregivers, some authors have analysed the internal factors of the Caregiver Burden Interview (CBI) (Zarit et al, 1986), reporting that adult children experienced stronger feelings of guilt (Ankri et al, 2005;Turró-Garriga et al, 2008;Sanders et al, 2008).…”
Section: Empirical Researchmentioning
confidence: 99%
“…Se ha considerado que la escala de Zarit abarca todos las dimensiones del síndrome del cuidador y ha sido validada en varios idiomas, incluyendo el español (23,24). Ha mostrado ser transculturalmente válida en Colombia (25), y tener una adecuada validez de apariencia, de contenido y de constructo en diferentes adaptaciones lingüísticas (26,27).…”
Section: Escala De Sobrecarga Del Cuidadorunclassified
“…Según Gort, et al, en las diferentes preguntas de la escala de Zarit se exploran diversos campos: la sensación de sobrecarga experimentada por el cuidador, el abandono del autocuidado tanto en temas de salud como en autoimagen, la vergüenza ante la presencia o comportamiento del familiar enfermo, la irritabilidad ante la presencia del familiar, el miedo por los cuidados o el futuro del familiar, la pérdida de rol social y familiar al tener que asumir el de cuidador, la alteración de la economía y el sentimiento de culpabilidad generado por no hacer lo suficiente (21). Sin embargo, Ankri, et al, mediante el uso de un análisis factorial exploratorio determinó sólo tres dominios de utilidad para los médicos tratantes que enfrentan a estos cuidadores: efectos en la vida personal y social de los cuidadores, carga psicológica y sentimientos de culpa (24).…”
Section: Escala De Sobrecarga Del Cuidadorunclassified